DIGITAL COMPETENCES OF JUNIOR BACHELORS IN AGRONOMY - Yevstratiev, Yevstratiev (Educological discourse, 2020)
The article deals with the introduction of digital competences in the educational process of junior bachelors in agronomy. The model of development of digital skills of the population of the EU countries (EU Digital Competence Framework for Educators), the plan of the European model of digital competences for education is analyzed. The traditional model of education is concerned with knowledge achieving and today it does not satisfy either the job market or students. Today, Ukrainian education is being transformed in line with world requirements, as evidenced by the introduced reforms in the system of education and the adoption of a new law on education. The paradigm of education is being transformed; models and learning approaches are changing. And, in general, research shows that the overall vector of change is aimed at developing digital competence, social and communication skills for successful activities in the digital world. The examples of formation of digital competences in the process of training of modern specialists around the world and in Ukraine are given; taking into account the Framework of digital competence, the decision of the Ministry of Education and Science of Ukraine on reforming the education system is analyzed. According to the analysis of the labour market of the agricultural sector which there is a problem of non-compliance of the national structure of vocational education with the prospective needs of the agricultural labour market in terms of qualification level and structure of professional competencies of graduated agronomists, the main reason for which is non-taking into account the consideration in the process of preparation of the current state of use of information technologies in the areas of agricultural industry. Comparison of special (professional, subject) competences in accordance with the existing standard of training of junior bachelors in agronomy and the proposed list of competencies formed in accordance with current trends in global digitalization, including agricultural production is carried out. A thematic structure of the content of training for the formation of digital professional competencies for future agronomists is proposed. The issue of teaching a new discipline in terms of professional affiliation of the teacher is raised.